Antifungal Activity, Phytochemical Analysis of Solanum nigrum (L.) - An Important Antiulcer Medicinal Plant - C.V.Naidu3*, T.M.Sridhar1, P.Josthna2 and (Journal of Ecobiotechnology, 2011)
Solanum nigrum (L.) is commonly known as Ã¢â‚¬Å“Blacknight shadeÃ¢â‚¬Â and is belongs to solanacae family. The herb is antiseptic, anti dysenteric, antidiuretic and it has very important gastric ulcerogenic activities. Three solvent extracts from leaf,seed and roots of Solanum nigrum were assayed for antifungal activity against fungal strains such as Penicillium notatum, Aspergillus niger, Fuserium oxisporium and Trichoderma viridae. The zone of inhibitions was compared with the standard antibiotics. Phytochemical screening of the crude extracts reveals the presence of various secondary compounds such as alkaloids, flavonoids, steroids, tanins and phenols. The organic solvent extracts (ethanol, methanol and ethyl acetate) of seeds were exhibited strong antifungal activity against all the tested fungal strains compared to leaf and root extracts. Among all the extracts ethyl acetate seed extract showed high antifungal activity (8.0-16.0mm zone of inhibition) on all the tested fungal strains and relatively lowest MIC value in the range of (2.0-6.0mg/ml) were obtained with ethanol seed extracts.